Accepting the Challenge—Moderate-Intensity Exercise with Individuals with Dementia: A Case Series. (July 2019) - Dawson, Nicole; Judge, Katherine
Background and purpose: The global impact of dementia demands a response from researchers and clinicians to not only assist with prevention and a cure, but also to assist in the management of symptoms related to this progressive disease. The purpose of this case series is to highlight the participation of 3 individuals with varying levels of dementia in a moderate-intensity functional exercise program. Intervention: The intervention, developed using principles from exercise science and a Strength-Based Approach, consisted of 24 sessions of moderate-intensity exercises delivered in participant's home. Outcomes: Each participant completed a pre- and post-assessment including gait speed, strength, balance, depressive symptoms, cognition, and perceived difficulty with activities of daily living. Despite various clinical presentations, each participant successfully completed all 24 sessions with noted improvements in at least two measures. Discussion: These findings highlight the flexibility of using the Strength-Based Approach to enhance participation in a standardized exercise program.